2013
DOI: 10.1080/14783363.2013.839348
|View full text |Cite
|
Sign up to set email alerts
|

What service excellence can learn from business excellence models

Abstract: Service excellence is recognised as a means to delight customers, enhance customer loyalty, and build long-term customer relationships. The existing service excellence models focus on the perspective of customers but fail to provide a systematic approach to implementation. On the other hand, business excellence models (BEMs), such as the European Foundation for Quality Management (EFQM) and Baldrige criteria for performance excellence (BCPE), provide a highly structured managerial approach. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Notwithstanding this economic decision factor, our analysis reveals the benefits of a continuous improvement paradigm, whereby a commodity of service increases customer satisfaction and economic viability. These factors concur with prior research findings in the TQM literature [21,24,26] where TQM is identified as representative of an integrated management philosophy. Adoption of the conventions through membership of an operator compliance scheme can offer an opportunity to drive a change in organisational culture in the freight transport sector.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Notwithstanding this economic decision factor, our analysis reveals the benefits of a continuous improvement paradigm, whereby a commodity of service increases customer satisfaction and economic viability. These factors concur with prior research findings in the TQM literature [21,24,26] where TQM is identified as representative of an integrated management philosophy. Adoption of the conventions through membership of an operator compliance scheme can offer an opportunity to drive a change in organisational culture in the freight transport sector.…”
Section: Discussionsupporting
confidence: 87%
“…Ebrahimi and Sadeghi [21] argue that TQM represents an integrated management philosophy, whereby quality is mandatory in meeting customer expectations by retaining customer focus (see also: [22][23][24][25][26]). Meanwhile, others identify the multidimensional aspects of TQM, indicating its ability to be "cherry picked" for application by small businesses [18].…”
Section: Applying Aspects Of Tqmmentioning
confidence: 99%
“…However, Wu and Zhang (2013) in an analysis of explorative and exploitative quality management practices showed that, while firms can benefit from QM practices with both types of orientations, they may emphasize one orientation over the other. In a similar vein, several authors (Williams et al, 2006;Gómez et al, 2011;Sampaio et al, 2012;Asif and Gouthier, 2014) have highlighted that the EFQM model is not prescriptive, and therefore does not require the use of specific practices. Consequently, multiple approaches or different ways of adopting the EFQM model may be expected, since organizations can in principle achieve high levels of excellence by excelling in some criteria, even though they are rated poorly on others.…”
Section: Introductionmentioning
confidence: 99%
“…Rusjan 2005;Sampaio et al, 2012;Asif and Gouthier, 2014) state that the EFQM suggests several approaches in the path towards excellence. In their view, by using the model, organizations can develop best practices in a coherent way but, at the same time, given the non-prescriptive nature of the model, organizations can develop their own "specific" approach.…”
Section: The Adoption Of the Efqm Excellence Model By Leading Organizmentioning
confidence: 99%
“…It allows you to get an idea of how far the organization has progressed through the implementation of the concept of management through quality and what it must do to achieve success (Recha, 2009). Many authors (Rusjan, 2005, Sampaio et al 2012, Asif et al, 2014 claim that the EFQM model proposes several different approaches on the road to excellence . In their view, organizations can develop best practices in a coherent way using the model.…”
Section: Improvement Of the Organization In The Aspect Of Self-assessmentioning
confidence: 99%